Floriculture and the Role of Women in Nagaland : A Case Study - Pusa, Khriemenuo; Giribabu, M. (Arthshastra Indian Journal of Economics & Research, 2016)
Cultivation of flowers in Nagaland has been in practice since time immemorial, and production and marketing of cut flowers was confined to a small area. However, since 2004-05, under the active support of Horticulture Mission for North-Eastern and Himalayan states (HMNEH), more area was brought under floriculture for commercial purposes. Increase in the domestic demand for fresh-cut flowers and support from the state government is encouraging more women to take up flower cultivation on a commercial basis. The district of Kohima was selected for the present study. This study was done on primary data collected from 100 flower growers interviewed using a pre-tested questionnaire. Simple tabulation and regression model was used to analyze the data collected. With the commercialization of floriculture products, the floriculture sector has now become one of the fastest growing segments of horticulture, opening ways for Naga women and unemployed female youths to earn a living by engaging themselves in activities which were earlier a mere hobby for them, pushing the economy towards development. The flower industry in Nagaland, being a fresh industry, is facing many challenges and shortcomings. Thus, efforts have been made to study the extent of women empowerment through floriculture, employment opportunities, income generation, and challenges associated with it.